ASME 2007 Summer Bioengineering Conference 2007
DOI: 10.1115/sbc2007-175333
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanical and Computational Investigation on the Effects of Conduit Orientation on the Strength of Massive Bone Allografts

Abstract: Massive allograft bone is the primary source of bone graft material for use in limb salvage procedures after oncological tumor resection. However, allograft bone has been found to incorporate slowly into host bone resulting in allograft susceptibility to non-union, fracture, infection and fatigue failure. Clinical studies have shown that massive allograft bone has a 50% to 75% success rate at 10 years [1].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…The material parameters, stress, and modulus were unaffected by increasing freeze-thaw cycles or even by freeze-drying. These results are in line with those of other authors regarding soft tissue [6,8,9] and hard tissue [10,13,14] as a result of freezing and thawing cycles. Two previous studies [12,17] found that processing and storage caused freeze-dried allograft bone to be weaker, but we did not compare our samples with the same control group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The material parameters, stress, and modulus were unaffected by increasing freeze-thaw cycles or even by freeze-drying. These results are in line with those of other authors regarding soft tissue [6,8,9] and hard tissue [10,13,14] as a result of freezing and thawing cycles. Two previous studies [12,17] found that processing and storage caused freeze-dried allograft bone to be weaker, but we did not compare our samples with the same control group.…”
Section: Discussionsupporting
confidence: 93%
“…Two studies showed torsion and bending properties of freeze-dried allograft bone were weaker after processing and storage [12,17]. In contrast, other studies found as many as five freeze-thaw cycles do not affect the biomechanical properties of cancellous bone [10,14] and long-term freezing reduces immunogenicity of grafts but does not decrease the biomechanical properties [13]. Thus, additional research on how freezing cycles affect bone biomechanics and morphology is clearly warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Contact was modeled as rough (i.e., relative slip between contact surfaces was restricted) in accordance with the experimental use of rough platens. No other boundary conditions or kinematic constraints were applied to the bone sections, which were constrained only by contact with the platens, in accordance with experimental protocol (Santoni et al, 2007). The maximum in-plane principal stress and platen displacement were predicted and reported.…”
Section: Article In Pressmentioning
confidence: 99%
“…The diametral compression test method has been used extensively to quantify the tensile strength of brittle solids such as ceramics (DeWith, 1984;Sinha and Dhoopar, 1986;Rudnick and Hunter, 1963), and recently developed ASME standard WK88 addresses strength testing of circular rings for brittle materials (ASTM Standard, 2003). Two-point diametral compressive forces applied to closed cylindrical sections result in the generation of maximum in-plane principal stresses at the inner surface along the load plane (Santoni et al, 2007). Testing of biologically derived samples, however, entails a number of added complications, such as the non-circularity of bone sections, ambiguity of load orientation during testing, thickness variation in a section, and size and shape variation between sections in a single sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation